A content analysis of HPV related posts on instagram - Corey H. Basch; Sarah A. MacLean (Taylor & Francis Group, 2019)
Human papillomavirus, or HPV, is the most common sexually transmitted disease in the United States. Despite the potential deleterious effects of HPV, vaccine uptake remains suboptimal. One potential venue for educating the public about HPV and vaccinations is through social media such as the widely used Instagram platform. Given the widespread reach of a platform with such a vast user base, the aim of this study was to describe posts related to HPV on Instagram. Content categories were established using fact sheets from the Centers for Disease Control HPV index page. Important content categories were created and the resultant coding sheet was used to analyze posts from the hashtag #HPV. Of the 150 posts analyzed, 53 posts (35%) mentioned the HPV vaccine. More were pro-vaccine (28%) versus anti-vaccine (7%). Posts mentioned the association of HPV with cancer (35%) and prevention of HPV (32%). Posts with a higher number of likes were more likely to mention cancer (p = 0.016) and HPV screening (p = 0.041). Among those that mentioned the HPV vaccine, posts that were anti-vaccine were less likely to mention prevention (p < 0.001) and cancer (p < 0.001). As new technology emerges and is widely adopted, health professionals should be aware and adept at using what is popular to influence given audiences. This applies to adolescents in particular, who, by and large are frequent users of technology for communication.